(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
The possible identity between functional and equivalence classes is consistent with the proposal that all elements arbitrarily related in the contingence can participate in the classes. The present study investigated stimulus class formation via repeated reversals of simple discrimination procedure - RRSD - and its expansion through both RRSD and matching to sample (MTS) procedure. Two children diagnosed with Autism Spectrum Disorder participated in this study. We carried out RRDS training (stimulus sets A, B, C, and D); tests for functional class and equivalence class formation; MTS and RRSD training with new stimuli; and tests for class expansion in both procedures. Both participants showed evidence of class formation and expansion. This data suggest that findings documenting functional and equivalence classes reflect the same behavioral phenomena (substitutability of arbitrarily related elements) via different procedures.